Surgical Management of Giant L2 Adrenal Neuroblastoma in Adult Male - Bikash Bikram Thapa; Sanjay Yadav; Sujit Pant; Pratik Rajkarnikar; Pankaj Mandal (Case Reports in Urology)
Neuroblastoma is an embryonal malignancy that arises from neural crest cells. Adult adrenal neuroblastoma is a rare disease, and less than 100 cases were reported in the literature. Adult neuroblastoma commonly presents with abdominal (retroperitoneal) lump and pain. A 35-year-old male patient presented with a giant (20 cm×17 cm×12 cm) nonfunctional left adrenal mass. He underwent en-bloc surgical excision of the left adrenal gland along with the left kidney. Histopathological examination revealed adrenal neuroblastoma (stage 2B, L2). We present here the surgical management of the rare adult adrenal neuroblastoma.